Simulation optimization of truck queue loading process discrete simulation approach with Promodel Software at PT. XYZ - Ardiansyah, Rahandi; Akbar, Muhammad Ali; Hijuzaman, Osep (Universitas Mercu Buana, 2024)
Warehouses have an important role for companies, including PT. XYZ located in Karawang. This research aims to optimize truck queues in the loading and loading process at PT. XYZ uses a discrete simulation approach with ProModel software. The problem of long truck queues and high delivery order (DO) waiting times disrupted the operational efficiency of distribution facilities. In this study, 3 simulation scenarios were tested to evaluate the impact of adding loading docks on throughput, waiting time, and resource usage by removing the Delivery Order (DO) waiting time. The data collected includes loading and loading process time, namely truck arrival data, warehouse information data, transport truck information data, and product information data implemented using ProModel software and then validated through replication tests and validity tests using the t-test method. The simulation results show that using scenario 1, the addition of one loading dock increases throughput by 45% and reduces the average wait time from 18 minutes to 9.3 minutes per truck. In addition, the use of resources becomes more optimal, increasing overall productivity. With these results, the study concludes that the addition of loading dock is an effective solution to overcome bottlenecks in the loading process at PT. XYZ, which can be implemented to improve operational efficiency.